Hubungan Yoga sebagai Induksi Alami terhadap Proses Persalinan Normal di PMB Nani Suryanti Kota Palembang - Rosdiana, Meta; Fristika, Yessy Octa (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Yoga really helps the birth process, namely in terms of physical and psychological readiness for pregnant women, reducing anxiety during pregnancy and the birth process, improving sleep quality, as a natural induction, reducing pain during labor, speeding up the first stage of labor, speeding up the second stage of labor, and making normal delivery without complications. This research aims to see the relationship between Yoga as a Natural Induction to the Normal Childbirth Process at PMB Nani Suryanti, Palembang City in 2023. This research uses a quantitative analytical design using primary data using a cross sectional approach. The research sample was taken by total sampling. The number of samples in this research was 22 samples. There is a significant relationship between Yoga as a Natural Induction and the Normal Childbirth Process, namely P-Value = 0.000. The results of this study recommend that other researchers who intend to conduct research on the relationship of Yoga as a natural induction to the normal birth process involve more samples and variables studied with different designs and use instruments that have standard validity and reliability values.